TUBERCULOUS SPONDYLITIS IN A 20 YEARS-OLD MAN WITH PULMONARY LESIONS: A CASE REPORT - Firdausi Nuzulah, Selly; Andy Wijaya, Rike; Arif Kadarman, Jan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Tuberculosis caused by Mycobacterium tuberculosis (Acid-Fast Bacilli/AFB) the disease infects the lungs (pulmonary tuberculosis), but it can also infect other organs (extrapulmonary tuberculosis). Tuberculous spondylitis or Pott's disease is an infection of Mycobacterium tuberculosis in the vertebrae (extrapulmonary tuberculosis). The early diagnosis of tuberculous spondylitis is difficult and often confused with spinal neoplasms or other pyogenic spondylitis. Case presentation: Our patient admitted to Dr. Ramelan Navy Hospital Surabaya with the chief complaint of bump in the lower right back since 4 months before entering the hospital, the bump felt painful (and a Wong- Baker pain scale of 4) when coughing and when touched, lump palpable with a soft consistency and 12 cm in diameter. Patient can move their legs freely and there are no limitations on the patient's range of motion. Defecate and urinate within normal limits. This patient has demonstrated a stable deformity with severe kyphosis with a 27 sagittal angulation without any neurological deficits.Conclusions: This report highlights to clinicians the value of a high index of suspicion and careful history taking in tuberculous spondylitis; and how a combination of nonspecific findings helped reach an early diagnosis. Because the clinical manifestations of TB spondylitis differ, various methods, including thoracolumbosacral X-ray and MRI with contrast, are required to confirm the disease. As a result, an interdisciplinary collaborative team is required to achieve optimal patient outcomes and to prevent long-term sequalae